QUO VADIS PENGAJARAN ILMU EKONOMI? - Santoso, Bagus (Journal of Indonesian Economy and Business, 2002)
This paper examines the teaching curriculum at the Faculty of Economics Gadjah Mada University and its future development. Better quality of teaching materials on quantitative as well as qualitative methods should be the final goal. Recently there were âtalksâ among faculty members to change the name of the faculty of economics to became Faculty of Economics and Business. This paper argues against the idea.Keywords: Neoclassical and Keynesian Economics, Economics Teaching.